Sarcoidosis: A Prospective Observational Cohort from Northern Alberta - Vethanayagam, Dilini; Peters, Jillian; Saad, Emad; Mulchey, Kimberley; Gillson, Ashley-Mae; McNab, Brian; Farr-Jones, Maxine; Hruczkowski, Tomasz; Blevins, Gregg; Coulden, Richard; Oudit, Gavin; Beach, Jeremy (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2020)
Introduction: Sarcoidosis is a multi-system disease reported to occur with a higher prevalence in Alberta than many other health jurisdictions within and outside of Canada. The reasons for this higher prevalence are currently not known. Exposure to beryllium can result in a clinically and radiologically identical disease to sarcoidosis. The purpose of our study was to identify patterns with potential occupational or environmental exposures to beryllium amongst individuals with sarcoidosis in Alberta through a tertiary referral center.Methods: A prospective observational study was carried out at the University of Alberta Hospital. Patients with confirmed sarcoidosis (stages 0-4) were recruited from subspecialty clinics (Respirology, Cardiology, Neurology and Occupational Health).  A predetermined list of industries thought to involve potentially relevant exposures for the development of sarcoidosis was used to capture current and previous exposure history.  Results were entered into a database and where possible verified by comparing with existing electronic medical records (including histories, physical examination, diagnostic imaging and physiology).Results:  A total of 45 patients were recruited, 25 men and 20 women. Of these, 84% of participants reported working in or being exposed to an industry/environment suspected of contributing to development of sarcoidosis over their lifetime. The most frequently reported exposures were within farming and agriculture (27%), oil and gas (20%), metalworking and handling animals (18%).Conclusions: Amongst this cohort, a high proportion reported working with a potentially relevant exposure. Individuals being assessed for sarcoidosis should have their most responsible physician elicit a detailed work and environmental history.